Interpretation : An Essay in the Philosophy of Literary Criticism - Juhl, P. D. (Peter D.), 1946- (Book collections on Project MUSE., 1980)
This book provides and defends an analysis of our concept of the meaning of a literary work. P.D. Juhl challenges a number of widely held views concerning the role of an author's intention: the distinction between the real and the implied" author; and the question of whether a work has not one correct, but many acceptable interpretations. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905